Discovery of an excess of Halpha emitters around 4C 23.56 at z=2.48 - Tanaka, I.; De Breuck, C.; Kurk, J.; Taniguchi, Y.; Kodama, T.; Matsuda, Y.; Packham, C.; Zirm, A.; Kajisawa, M.; Ichikawa, T.; Seymour, Nick; Stern, D.; et al. (2011)
We report on the discovery of a significant excess of candidate Hα emitters (HAEs) in the field of the radio galaxy 4C 23.56 at z = 2.483. Using the MOIRCS near-infrared imager on the Subaru Telescope we found 11 candidate emission-line galaxies to a flux limit of ~7.5 × 10−17 erg s−1 cm−2, which is about 5-times excess from the expected field counts with an ~3-σ significance. Three of these have been spectroscopically confirmed as redshifted Hα at z = 2.49. The distribution of candidate emitters on the sky is tightly confined to a 1.2-Mpc-radius area at z = 2.49, locating 4C 23.56 at the western edge of the distribution. An analysis of the deep Spitzer MIPS 24 μm imaging shows that there is also an excess of faint MIPS sources. All but two of the 11 HAEs are also found in the MIPS data. The inferred star-formation rate (SFR) of the HAEs based on the extinction-corrected Hα luminosity (median SFR ~> 100 Msolar yr−1 ) is similar to those of HAEs in random fields at z ~ 2. On the other hand, the MIPS-based SFR for the HAEs is on average 3.6-times larger, suggesting the existence of star-formation significanly obscured by dust. A comparison of the Hα-based star-formation activities of the HAEs in the 4C 23.56 field to those in another proto-cluster around PKS 1138−262 at z = 2.16 reveals that the latter tend to have fainter Hα emission despite similar K-band magnitudes. This suggests that star-formation may be suppressed in the PKS 1138−262 protocluster relative to the 4C 23.56 protocluster. This difference among the HAEs in the two proto-clusters at z > 2 may imply that some massive cluster galaxies are just forming at these epochs with some variation among them.